Enhancing public Services through Agile Governance: A case study of the online queue application at RSUD Sawerigading Palopo city - Lestari, Indah; Abdullah, Muh Tang; Hasniati, Hasniati; Nara, Nurdin (Edelweiss Applied Science and Technology, 2025)
Agile governance has emerged as a crucial approach for public service organizations to enhance their responsiveness to rapidly changing environments and citizen needs. This study examines the application of Agile Governance principles, specifically the Business-Driven and Human-Focused principles, in the implementation of an online queue system at RSUD Sawerigading Palopo City, Indonesia. Employing a qualitative case study design, data were collected through observations, open-ended interviews with nine key informants, and document analysis. The findings reveal that the hospital has successfully aligned its strategic decisions with organizational goals, as demonstrated by the introduction of the queue application to improve service efficiency and patient satisfaction. Moreover, the hospital has actively engaged the community in the development and assessment of the application, fostering a sense of ownership and trust among the public. However, the study also identifies areas for improvement, such as enhancing network stability, expanding application accessibility, and incorporating digital payment options. The successful application of Agile Governance principles at RSUD Sawerigading Palopo City serves as a valuable example for other public service organizations seeking to adapt to the increasingly technology-driven landscape and improve their responsiveness to community needs. Future research should explore the application of Agile Governance principles in different public service contexts, investigate the long-term impact on organizational performance and public trust, and identify effective strategies for overcoming implementation challenges.